Hysteresis‐Free and High‐Sensitivity Strain Sensing of Ionically Conductive Hydrogels. Issue 2 (22nd December 2022) - Song, Jiwoo; Mou, Chenchen; Balakrishnan, Gaurav; Wang, Yingqiao; Rajagopalan, Mahathy; Schreiner, Audrey; Naik, Durva; Cohen-Karni, Tzahi; Halbreiner, M. Scott; Bettinger, Christopher J.
Abstract : Hydrogels are promising materials for soft and implantable strain sensors owing to their large compliance ( E < 100 kPa) and significant extensibility ( ε max > 500%) compared with other polymer networks. Further, hydrogels can be functionalized to seamlessly integrate with many types of tissues. However, most current methods attempt to imbue additional electronic functionality to structural hydrogel materials by incorporating fillers with orthogonal properties such as electronic or mixed ionic conduction. Although composite strategies may improve performance or facilitate heterogeneous integration with downstream hardware, composites complicate the path for regulatory approval and may compromise the otherwise compelling properties of the underlying structural material. Herein, hydrogel strain sensors composed of genipin‐crosslinked gelatin and dopamine‐functionalized poly(ethylene glycol) for in vivo monitoring of cardiac function are reported. By measuring their impedance only in their resistive regime (>10 kHz), hysteresis is reduced and the resulting gauge factor is increased by ≈50× to 1.02 ± 0.05 and 1.46 ± 0.05 from ≈0.03 to 0.05 for PEG‐Dopa and genipin‐crosslinked gelatin, respectively. Adhesion and in vivo biocompatibility are studied to support implementation of strain sensors for monitoring cardiac output in porcine models. Impedance‐based strain sensing in the kilohertz regime simplifies the piezoresistive behavior of these materials and expands the range of hydrogel‐based strain sensors. Abstract : Ionically conductive hydrogels are promising materials for biointerfacing but are limited in electronic‐sensing capabilities without potentially toxic conductive fillers. By measuring their impedance only in their resistive regime, hysteresis is reduced and gauge factor is improved by a factor of 50. Biocompatible genipin‐crosslinked gelatin and dopamine‐functionalized poly(ethylene glycol) are used as model hydrogels for this study.